MORAL EDUCATION IN THE CONTEXT OF STUDENTS' OLYMPIAD MOVEMENT - A. I. Popov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the issue of moral education of the technical higher school students, as well as the new pedagogical instruments and technologies of fostering the new technical elite. The author considers a widespread development of students' Olympiad movement as an effective way of their involvement in creative community service. Unlike the secondary and high school Olympiad movement, its development at the higher school level is far from perfect. The author emphasizes the difference between the regular Olympiad cycles, aimed at developing students' creative competences, and sporadic contests, devoid of cognitive motivation; hence he advocates the firm regulations on the Olympiad procedures and obligatory participation of higher schools in the above movement. The paper considers the Olympiad process and components as a new form of the higher school training, and briefly describes a specific organizational technique based on the competence and activity approaches. Additionally, the author points out a need for balancing the collective cognitive activity and competitiveness in educational process. The research findings can be used for educational process elaboration and students' creativity training in the technical higher school.